Herbaria are a major frontier for species discovery. - Bebber, D; Carine, M; Wood, JR; Wortley, A; Harris, D; Prance, G; Davidse, G; Paige, J; Pennington, T; Robson, N; Scotland, R (2010)
Despite the importance of species discovery, the processes including collecting, recognizing, and describing new species are poorly understood. Data are presented for flowering plants, measuring quantitatively the lag between the date a specimen of a new species was collected for the first time and when it was subsequently described and published. The data from our sample of new species published between 1970 and 2010 show that only 16% were described within five years of being collected for the first time. The description of the remaining 84% involved much older specimens, with nearly one-quarter of new species descriptions involving specimens >50 y old. Extrapolation of these results suggest that, of the estimated 70,000 species still to be described, more than half already have been collected and are stored in herbaria. Effort, funding, and research focus should, therefore, be directed as much to examining extant herbarium material as collecting new material in the field.